2013
DOI: 10.12691/env-1-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum Exploration and Production: Past and Present Environmental Issues in the Nigeria’s Niger Delta

Abstract: Petroleum exploration and production in the Nigeria's Niger Delta region and export of oil and gas resources by the petroleum sector has substantially improved the nation's economy over the past five decades. However, activities associated with petroleum exploration, development and production operations have local detrimental and significant impacts on the atmosphere, soils and sediments, surface and groundwater, marine environment and terrestrial ecosystems in the Niger Delta. Discharges of petroleum hydroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(66 citation statements)
references
References 98 publications
(109 reference statements)
1
65
0
Order By: Relevance
“…1 Oil platforms, used as a proxy for presence of hydrocarbon industry activity, were identified as the most influential anthropogenic threat in the overall CUI, indicating that hydrocarbon development may be of most risk to humpbacks in this region. The presence of industrial development, namely oil and gas exploration and production, is relatively high in these areas and is a large source of revenue for many countries in the region (Ite, Ibok, Ite, & Petters, 2013;NIMASA, 2018;Udie, Bhattacharyya, & Ozawa-Meida, 2018; ejatlas.org). Tagged humpbacks travelled through areas of oil platforms off the coast of Gabon, where the model also identified 1 https ://www.fishe ries.noaa.gov/natio nal/marine-life-distr ess/2016-2019-humpb ack-whale-unusu al-morta lity-event-along-atlan tic-coast high breeding habitat suitability and high CUI scores (Figure 4b) .…”
Section: Overlap With Cumulative Anthropogenic Activitiesmentioning
confidence: 99%
“…1 Oil platforms, used as a proxy for presence of hydrocarbon industry activity, were identified as the most influential anthropogenic threat in the overall CUI, indicating that hydrocarbon development may be of most risk to humpbacks in this region. The presence of industrial development, namely oil and gas exploration and production, is relatively high in these areas and is a large source of revenue for many countries in the region (Ite, Ibok, Ite, & Petters, 2013;NIMASA, 2018;Udie, Bhattacharyya, & Ozawa-Meida, 2018; ejatlas.org). Tagged humpbacks travelled through areas of oil platforms off the coast of Gabon, where the model also identified 1 https ://www.fishe ries.noaa.gov/natio nal/marine-life-distr ess/2016-2019-humpb ack-whale-unusu al-morta lity-event-along-atlan tic-coast high breeding habitat suitability and high CUI scores (Figure 4b) .…”
Section: Overlap With Cumulative Anthropogenic Activitiesmentioning
confidence: 99%
“…Owolabi and Okonkwo (2015) and Renouard (2011) argued and concluded that the region is experiencing increases in social inequality, worsened health and economic condition, and water pollution and soil degradation, which has resulted in the reductions in wildlife and fisheries. Ite et al (2013) and Ebegbulem, Ekpe, and Adejumo (2013) added that these outcomes are linked to the exploitation and production of oil and gas in the region. Hence, the resultant effect of oil producing companies' operations and activities by association.…”
Section: The Need For Sustainable Developmentmentioning
confidence: 99%
“…Oil drilling has resulted in repeated spills and significant environmental damage in areas such as the Niger River Delta (Ite et al, 2013) and will continue to threaten similar habitats globally ( Figure 7). Principles derived, and patterns described, from CONCORDE's interdisciplinary approach to identifying and quantitatively assessing key physical, biological, and geochemical processes acting in the nGOM are applicable to other pulsed, river-dominated systems, even though there may be differing ecological communities, volumes of river discharge, and degrees of oil extraction activities relative to the nGOM.…”
Section: Summary and Future Applications Of Concordementioning
confidence: 99%